Transformational Leadership In Public Sector Innovation; Toward An Elderly-Friendly City - Saadah, Maratun (Universitas Muhammadiyah Mataram, 2023)
The article examines the role of transformational leadership in public sector innovation, specifically in addressing the challenges of managing older people to build an elderly-friendly community. The research focuses on the leadership of Jambi Mayor in employing innovation to realize Jambi as an Elderly-Friendly City. This is a descriptive qualitative study that aims to identify new information related to the transformational leadership of Jambi Mayor in innovating an Elderly-Friendly City. The authors identified transformational leadership as a major style in carrying out innovation. The study found that Jambi City is continuously promoting the importance of creating elderly-friendly cities and communities through the leadership of its Mayor. The study found that transformational leadership practices played a significant role in the process of making Jambi City an Elderly-Friendly City. The mayor motivated civil servants to improve their attitudes and assumptions towards public health services. The research concludes that leadership styles have a direct impact on the level of innovation adopted and the success or failure of strategic responses.